2012
DOI: 10.1210/en.2011-2041
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure and Energetic Cost of Feeding Are Augmented after Roux-en-Y Gastric Bypass in Obese Mice

Abstract: Although the prevalence of obesity has increased dramatically throughout the world during the last 25 yr, its long-term control remains poor. Currently, only gastrointestinal weight loss surgery, especially Roux-en-Y gastric bypass (RYGB), is associated with substantial and sustained weight loss and resolution or significant improvement of diabetes mellitus and other metabolic obesity-induced complications. Clinical observations and recent studies have suggested that RYGB induces its effects by changing the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
6
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 40 publications
11
74
6
3
Order By: Relevance
“…24 Alternatively, clinical and experimental studies have clearly demonstrated that RYGB induces weight loss by altering physiological regulation of energy balance and metabolic function. 10,12,[25][26][27] Calorimetric measurements in a RYGB mice model revealed increased resting energy expenditure and postprandial thermogenesis as main causes for higher postoperative energy consumption. 27 Global metabolic changes in a non-obese rat model of RYGB were characterized by a decrease in faecal bile acids and a shift from protein degradation to putrefaction through decreased faecal tyrosine with concomitant increases in faecal putrescine and diaminoethane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Alternatively, clinical and experimental studies have clearly demonstrated that RYGB induces weight loss by altering physiological regulation of energy balance and metabolic function. 10,12,[25][26][27] Calorimetric measurements in a RYGB mice model revealed increased resting energy expenditure and postprandial thermogenesis as main causes for higher postoperative energy consumption. 27 Global metabolic changes in a non-obese rat model of RYGB were characterized by a decrease in faecal bile acids and a shift from protein degradation to putrefaction through decreased faecal tyrosine with concomitant increases in faecal putrescine and diaminoethane.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,[25][26][27] Calorimetric measurements in a RYGB mice model revealed increased resting energy expenditure and postprandial thermogenesis as main causes for higher postoperative energy consumption. 27 Global metabolic changes in a non-obese rat model of RYGB were characterized by a decrease in faecal bile acids and a shift from protein degradation to putrefaction through decreased faecal tyrosine with concomitant increases in faecal putrescine and diaminoethane. 10 These data led to the suggestion that human gut microbiota and their cross talk with host metabolism may have an important role for the metabolic conversion in patients with T2D after RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies were published in recent years addressing the correct analysis of energy expenditure data in animals of markedly differing body weight and body adiposity (98). In the case of RYGB rats, when energy expenditure determined by indirect calorimetry is corrected for body weight, energy expenditure is usually higher in RYGB rats than in shamoperated ad libitum-fed and weight-matched controls (19).…”
Section: Energy Expenditurementioning
confidence: 99%
“…Dig Surg 2014;31:13-24 DOI: 10.1159/000354319 21 induced changes in energy expenditure [53,[55][56][57][58][59] . Some but not all studies report increases in energy expenditure, but energy expenditure was often measured only over short time periods and then extrapolated to a 24-hour period; hence, true effects induced by RYGB may have been overlooked.…”
Section: Physiological Mechanisms Behind Rygb Surgerymentioning
confidence: 99%